2011
DOI: 10.1111/j.1600-0501.2011.02198.x
|View full text |Cite
|
Sign up to set email alerts
|

Resorption of deproteinized bovine bone mineral in a porcine calvaria augmentation model

Abstract: The model represents a pathologic situation of excess resorption of DBBM and bone in an augmented area. The underlying cellular mechanisms remain to be uncovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 19 publications
7
35
0
Order By: Relevance
“…An interesting finding was the pronounced resorption of DBBM in a few selected areas where fibrous tissue from the maxillary‐zygomatic suture was allowed to grow into the augmented volume (Figure A). A similar finding was reported in a recent study using a porcine calvarial model . From the present study it seems likely that DBBM particles hosted in an osseous environment may undergo only limited resorption whenever exposed to the marrow cavity, whereas particles captured in fibrous tissue early in the healing phase are at significant risk of complete degradation.…”
Section: Discussionsupporting
confidence: 91%
“…An interesting finding was the pronounced resorption of DBBM in a few selected areas where fibrous tissue from the maxillary‐zygomatic suture was allowed to grow into the augmented volume (Figure A). A similar finding was reported in a recent study using a porcine calvarial model . From the present study it seems likely that DBBM particles hosted in an osseous environment may undergo only limited resorption whenever exposed to the marrow cavity, whereas particles captured in fibrous tissue early in the healing phase are at significant risk of complete degradation.…”
Section: Discussionsupporting
confidence: 91%
“…The peri‐implant bone loss measured in this study is consistent with values reported in literature . Histomorphometric analysis, evaluating the resorption of deproteinized bovine bone mineral (DBBM) in a porcine calvaria augmentation model, revealed that more than 50% of the augmented DBBM has been resorbed after 12 weeks . Nevertheless, extraction sockets augmented with a xenogeneic material reveal decreased loss of bone at the buccal plate than nonaugmented sites .…”
Section: Discussionsupporting
confidence: 88%
“…The presence of MNGCs on the surface of DBBM particles has been documented in several other clinical as well as animal studies 20,21,30,31,33,40,42‐46 . Most often, TRAP staining has been used to determine whether these MNGCs could be classified as osteoclast‐like cells or other cells from the macrophage‐monocyte lineage.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that DBBM particles have a low substitution rate only when the particles are osseointegrated, since pronounced resorption has been observed when DBBM was embedded in fibrous tissue during early healing 44‐46 . This observation has clinical implications for contour augmentation.…”
Section: Discussionmentioning
confidence: 99%